A Clinical Case of Takotsubo Syndrome in the Early Postoperative Period of Rhinoplasty - S. A. Boldueva; V. S. Feoktistova; D. S. Evdokimov; A. A. Kozak; P. V. Lisukova (Архивъ внутренней медицины)
Takotsubo syndrome (TS) is an acute reversible left ventricular myocardial dysfunction caused by an emotional or physical trigger. In the perioperative period, TS is in some cases induced by various psychological factors, such as stress before/after surgery, and non-psychological factors, such as drug administration. This article describes the clinical observation of takotsubo syndrome that developed in the early postoperative period of rhinoplasty